2019
DOI: 10.3390/jcm8122155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of A Six Week Training Program on Ventilatory Efficiency, Red Blood Cell Rheological Parameters and Red Blood Cell Nitric Oxide Signaling in Young Sickle Cell Anemia Patients: A Pilot Study

Abstract: Patients with sickle cell anemia (SCA) show impaired ventilatory efficiency, altered blood rheology, high levels of oxidative/nitrosative stress and enhanced hemolysis with large amounts of circulating free hemoglobin, which reduces nitric oxide (NO) bioavailability. The aim of the study was to investigate whether physical exercise could improve these physiological and biological markers described to contribute to SCA pathophysiology. Twelve SCA patients participated in a controlled six weeks training program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Several approaches to mitigate the harmful effects of oxidative stress in SCD have been proposed such as use of antioxidants ( 82 ), neutralization of products of hemolysis with haptoglobin (Hp) and hemopexin (Hpx) ( 83 ) and moderate strength and endurance exercise therapy ( 84 ). Recent studies showed that increase in physical activity improves blood rheology, increases NO bioavailability and reduction in oxidative stress and hemolysis in mice ( 85 87 ) and SCD patients ( 88 ).…”
Section: Oxidative Stress and Hemolysis In Sickle Cell Diseasementioning
confidence: 99%
“…Several approaches to mitigate the harmful effects of oxidative stress in SCD have been proposed such as use of antioxidants ( 82 ), neutralization of products of hemolysis with haptoglobin (Hp) and hemopexin (Hpx) ( 83 ) and moderate strength and endurance exercise therapy ( 84 ). Recent studies showed that increase in physical activity improves blood rheology, increases NO bioavailability and reduction in oxidative stress and hemolysis in mice ( 85 87 ) and SCD patients ( 88 ).…”
Section: Oxidative Stress and Hemolysis In Sickle Cell Diseasementioning
confidence: 99%
“…Several studies documented improved exercise performance in SCA patients after moderate exercise training 1,5,7–9 . Anecdotally, Subject 1 in this study, the only one who demonstrated increase in peak VO 2 , reported engaging in regular exercise after starting voxelotor, but this was not prospectively or objectively documented.…”
Section: Discussionmentioning
confidence: 61%
“…Sickle cell providers are often asked to provide sports clearance for students with SCA, but no athletic guidelines are available for SCA, as there are for SCT 3,4 . Additionally, regular exercise has been shown to benefit patients with SCA 1,5–9 . Thus, understanding exercise capacity in SCA is increasingly necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,18 However, recent studies have demonstrated the safety and feasibility of endurance training in children and adults with SCD, with potential benefits for their functional capacity and quality of life. 2024 Our previous study 24 reported several muscle benefits after 8 weeks of endurance training, such as slight hypertrophy of type I muscle fibers. This specific adaptation of type I fibers is related to the nature of the moderate-intensity endurance training program which recruited this type of fibers in particular.…”
Section: Introductionmentioning
confidence: 99%